Review-Artikel: Zum aktuellen Stand des Plattformkapitalismus; Review Article: The Current Situation of Platform Capitalism - Heiner Heiland (Industrielle Beziehungen, 2018)
Die Plattform ist in den letzten Jahren sowohl eine zentrale Institution als auch wesentliche Metapher der gegenwärtigen Verfasstheit westlicher Gesellschaften geworden, so dass von einem ,,Plattformkapitalismus“ die Rede ist. Nachhaltige Auswirkungen zeigen sich in verschiedenen Sphären – darunter besonders zentral in der Organisation von Arbeit. Nach einer breiten medialen Thematisierung spiegelt sich das Phänomen auch in einer zunehmenden wissenschaftlichen Auseinandersetzung wider. Im folgenden Beitrag werden vier aktuelle Werke vorgestellt und diskutiert, die den englischsprachigen Diskurs wiedergeben. – – In recent years, the platform has become a pivotal institution as well as an essential metaphor of western societies' constitutions. Subsequently, the term “platform capitalism” has been created. The enduring consequences appear in different spheres – especially in the organisation of work. Having firstly become a key theme in the media, the phenomenon is now the subject of a growing scientific debate. In the following article, four current books are presented and discussed, each reflecting the discourse on the subject platforms in the English-speaking world.
Keywords: J40; O33; P12; 330; platform capitalism; digitalisation; future of work; organisation of work; crowdwork